Binding conditions: How are they derived? - Reuland, Eric (Proceedings of the 12th International Conference on Head-Driven Phrase Structure Grammar, 2005)
In this article I discuss binding conditions A and B. I show that importantproperties of binding need not be stipulated, but can be explained asconsequences of general properties of the computational system underlyinghuman language.